Strategies for the preservation and enhancement of traditional knowledge in Kyrgyzstan - Gulnara Botokanova; Gulnara Murzakhmedova; Meerim Tologonova (Clío, 2025)
The purpose of this study is to examine the features and strategies for preserving, enhancing and disseminating traditional knowledge in the modern information space. The comparative analysis conducted identified traditional knowledge as the knowledge of communities passed down through generations, characterised by subjectivity, reliance on qualitative data, oral transmission from the older generation to the younger, and the exploration of objects within their natural context. Many aspects of traditional knowledge have stood the test of time and can be utilized to address current challenges, including limited access to formal healthcare and the preservation of biodiversity. The preservation and enhancement of traditional knowledge are among the Kyrgyz government’s priorities, because such knowledge shapes the nation’s self-identity and enables the preservation of its uniqueness in a rapidly changing world. However, preserving traditional knowledge is a complex task that involves overcoming a number of challenges, including legal conflicts regarding the protection of traditional knowledge through copyright or patenting; insufficient public awareness of the role of traditional knowledge in preserving national identity; and biased attitudes towards certain communities and custodians of traditional knowledge.